20 years of Zootaxa: Tardigrada (Ecdysozoa: Panarthropoda) - Mcinnes, Sandra J.; Jørgensen, Aslak; Michalczyk, Łukasz (Zootaxa, 2021)
Over the last two decades, Zootaxa has hosted nearly 200 papers concerning tardigrade taxonomy, systematics, phylogeny, and evolution. A total of 160 researchers from all continents (except the Antarctic) published descriptions of almost 200 new taxa, mostly species, but also genera and higher taxonomic ranks, such as families and superfamilies. This editorial is dedicated to the late Professor Clark W. Beasley who was the first tardigrade Associate Editor for Zootaxa.